Optimizing the Potential of Leather Micro Industry through Innovation and Product Diversification by the Department of Industry, Trade, Energy, and Mineral Resources of Garut Regency - Juliati Prihatini; I Made Aldy Wijaya (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Raw materials for sheepskin products are easily obtained in Sukaregang, Kota Wetan Village because it is a leather industry center. The Department of Industry, Trade, Energy, and Mineral Resources (Disperindag ESDM) of Garut Regency strives to improve the welfare of micro-industry business actors from leather through innovation and product diversification. The purpose of this study was to determine efforts to optimize local potential through innovation and product diversification carried out by the department, as well as inhibiting factors and efforts to overcome inhibiting factors. This research method is qualitative descriptive. Data collection techniques with observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The theory used is the optimization theory according to Siringoringo. The results of the study indicate that business actors have several inhibiting factors in efforts to optimize local potential. Efforts made by the Disperindag ESDM of Garut Regency to overcome these inhibiting factors include adding employees, providing capital assistance, and providing training and mentoring for product marketing through digital media and e-commerce.